Komunikasi Organisasi dalam Kaderisasi di Partai Politik DPD Gerindra Kota Bandung - Indra Gumbira Rukmana (UPT Publikasi Ilmiah UNISBA, 2023)
Abstract. Organizational communication is very important for the sustainability of the organization, one of which is in a political organization, namely the Gerindra Political Party. In maintaining the existence of the party, Gerindra parties carry out regeneration because this is the core of the continuation of the organizational struggle. This study aims to determine the process of regeneration of the Gerindra Political Party in Bandung. This is to find out the training carried out in maintaining the solidity of cadres. To find out the party cadres carried by the Gerindra Political Party in the election are from honorary members. In conducting the research, the writer used a qualitative method with the Single Level Case Study approach and the Constructivism paradigm. The data collection techniques used were direct observation, in-depth interviews, literature study and online search, and documentation study. The results and conclusions of the author in the study were the process of regeneration carried out by the Gerindra party including regeneration which was carried out structurally, non-structurally, and through party wings. Coaching is carried out by strengthening cadres who occupy top management in the management and legislative candidates or legislative members as well as executive / executive candidates and there is the formation of small group tutorials. Gerindra party cadres who are nominated from honorary cadres are not necessarily promoted, but there is a reference to nominate candidates not only as a result of internal party selection but seeing the electability and popularity of these candidates to help raise the popularity and electability of the party. Abstrak. Komunikasi organisasi sangat penting bagi keberlangsungan organisasi, salah satunya di organisasi politik yaitu Partai Politik Gerindra. Dalam menjaga eksistensi partai, partai gerindra melakukan kaderisasi karena hal ini merupakan inti dari kelanjutan perjuangan organisasi. Penelitian ini bertujuan Untuk mengetahui proses kaderisasi Partai Politik Gerindra Kota Bandung. Untuk mengetahui pembinaan yang dilakukan dalam menjaga soliditas kader. Untuk mengetahui kader partai yang diusung Partai Politik Gerindra dalam pemilu berasal dari anggota kehormatan. Dalam melakukan penelitian penulis menggunakan metode kualitatif dengan pendekatan Studi Kasus Single Level dan paradigma Konstruktivisme. Teknik pengumpulan data yang digunakan yaitu Obeservasi langsung, Wawancara Mendalam, Studi Pustaka dan Penelusuran Online, serta Studi Dokumentasi. Hasil dan kesimpulan Penulis dalam Penelitian adalah proses kaderisasi yang dilakukan partai Gerindra meliputi kaderisasi yang dilakukan secara struktural, secara non struktural, dan melalui sayap-sayap partai. Pembinaan yang dilakukan dengan adanya pemantapan yang dilakukan untuk kader yang menempati top manajemen di kepengurusan dan calon legislatif atau anggota legislatif maupun calon eksekutif/eksekutif dan ada pembentukan tutorial kelompok kecil. Kader partai Gerindra yang diusung berasal dari kader kehormatan tidak serta merta diusung tetapi ada acuan untuk mengusung calon tidak hanya hasil dari seleksi internal partai tetapi melihat elektabilitas dan popularitas calon tersebut untuk membantu mengangkat popularitas dan elektabilitas partai.